IMPLEMENTATION OF THE PERFORMANCE ACCOUNTABILITY SYSTEM FOR GOVERNMENT INSTITUTION (SAKIP) TO IMPROVE THE PERFORMANCE OF GOVERNMENT INSTITUTION - Muhammad Istiyansyah Ulman Idris (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Performance accountability is an obligation for government institution to beresponsible of its success and failure in the implementation of organizational’smission which consist with strategic planning, performance planning, performancemeasurement, and performance reporting. This research aims to find out the effect ofthe implementation of performance accountability system for government institutiontowards the performance improvement in Provincial Government of South Sulawesi.Population used in this research is Provincial Government of South Sulawesi whichthis research used purposive sampling method. Based on that method, RegionalDevelopment Planning Board, Bureau of Organizational and Official Affairs, andInspectorate became sample in this research because it has its own roles inimplementing the performance accountability system for government institution inSouth Sulawesi. Data gathered by doing direct interview. Furthermore, the documentof performance accountability report for government institution in 2014 and 2015became the secondary data in this research. Data processing including data reduction,data data display, and drawing conclusion and verification. In implementing theperformance accountability system for government institution, there is a positiveeffect towards the performance of South Sulawesi Provincial Government whichbased on the performance planning each year. In addition, performance which deemedto be lacking is expected to improve in line with the results shown in the performanceaccountability report for government institution.Keywords: Performance Accountability Report for Government Institution, Performance Improvement, Provincial Government of South Sulawesi.